1980
DOI: 10.1007/bf00009008
|View full text |Cite
|
Sign up to set email alerts
|

Carotenoids in fish. XXVI. Pungitius pungitius (L.) and Gasterosteus aculeatus L. (Gasterosteidae)

Abstract: Material and methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1984
1984
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 8 publications
1
12
0
Order By: Relevance
“…The ¢nding that the colour expression of a male during interaction correlates with his colour expression prior to interaction suggests that contest-independent costs of red coloration or inherent properties of the male limit colour expression. Red coloration is due to carotenoids (Brush & Reisman 1965;Matsuno & Katsuyama 1976;Czeczuga 1980;Wedekind et al 1998), which are essential for the immune system to function properly (e.g. Lozano 1994).…”
Section: Discussionmentioning
confidence: 99%
“…The ¢nding that the colour expression of a male during interaction correlates with his colour expression prior to interaction suggests that contest-independent costs of red coloration or inherent properties of the male limit colour expression. Red coloration is due to carotenoids (Brush & Reisman 1965;Matsuno & Katsuyama 1976;Czeczuga 1980;Wedekind et al 1998), which are essential for the immune system to function properly (e.g. Lozano 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Crozier (1967) demonstrated that increasing proportions of the carotenoid astaxanthin were associated with increasing the intensity of red colouration in Sebastes species. Astaxanthin is the major nuptial pigment in all populations of G. aculeatus examined to date (Brush and Reisman 1965;Matsuno and Katsuyama 1976;Czeczuga 1980), so the suggestion that intermale variability in relative pigment concentrations may be reflected in intermale variability in nuptial colouration is not an unreasonable one. Since the effects of selection on the elaboration of the signal will be constrained by the mechanisms underlying signal production, knowledge of these mechanisms is of paramount importance.…”
Section: Temporal Fluctuations In Colour: Black (Melanin)mentioning
confidence: 94%
“…Changes in both the absolute amount of pigment present and the relative concentrations of different pigments may be responsible for these observed hue shifts. Czeczuga (1980) outlined the pigment profile of a population of freshwater three-spined sticklebacks in Poland. Within this population, developmental changes in the males' integumentary pigments entailed both a minor alteration in the types of carotenoids present and a major shift in the relative propor- tions of the remaining pigments.…”
Section: Temporal Fluctuations In Colour: Black (Melanin)mentioning
confidence: 99%
“…Perhaps the rate of fading of die red (which is due to carotenoids; Brush and Reisman, 1965;Czeczuga, 1980;Frischknecht, 1993;Matsuno and Katsuyama, 1976) is sufficiently long that die energetics of parental care (Sargent and Gross, 1986) are not strong enough to affect die red over a single breeding cycle. The unchanged maximum of red diroat color may point to die value of diis signal during die parental phase in attracting additional females and/or defending the territory and nest against intruders.…”
Section: Intensity Of Red Coloration and Conditionmentioning
confidence: 99%